Resource Allocation for Consumption, Savings and Investments among Polish Households - Fatuła, Dariusz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The main subject of this article was the analysis of data from national research on how Polish households share resources on consumption, savings and investments. The paper investigates which features of households influence how money is allocated. The analysis included the goals of saving and investing, and the needs respondents to a survey satisfied by these means. The results indicate that most of the surveyed households anticipate spending all income on consumption. Accumulated savings generally located in bank deposits are not initially earmarked for any particular purpose or goal. Savings and investments mostly satisfy the needs of security and the desire to possess increasing wealth. Self-realisation needs are more often satisfied by spending savings than by investing.